Anti-inflammatory activity and mechanisms of a lipid extract from hard-shelled mussel (Mytilus coruscus) in mice with dextran sulphate sodium-induced colitis. (May 2016) - Wang, Fenglei; Fu, Yuanqing; Cai, Wenwen; Sinclair, Andrew J.; Li, Duo
Highlights: Effect of HMLE on DSS-induced colitis in mice was assessed. HMLE regulated the production of NO, MPO, TNF-α, IL-1β, IL-6, and IL-10. The mechanism might rely on the modulation of the TLR-4/NF-κB pathway. Overall effect was comparable with standard anti-inflammatory drug SASP. Abstract: The anti-inflammatory effect of a lipid extract from hard-shelled mussel (HMLE) on dextran sulphate sodium (DSS)-induced colitis in mice was investigated. Salicylazosulphapyridine (SASP) and different doses of HMLE were administered by gastric gavage. HMLE significantly attenuated DSS-induced colitis disease activity index scores, tissue damage, splenic enlargement and colon myeloperoxidase accumulation. In addition, HMLE improved colon oxidative stress and production and expression of anti-inflammatory cytokine, interleukin (IL)-10, while HMLE inhibited the abnormal productions and mRNA expressions of pro-inflammatory cytokines, namely tumour necrosis factor-α, IL-1β, and IL-6, as well as the expression of key molecules in the toll-like receptor (TLR)-4/nuclear factor (NF)-κB signalling pathway. These findings suggest that HMLE has an anti-inflammatory effect on DSS-induced colitis, equivalent to that of SASP, and this effect might be related to the regulation of inflammatory mediators and key molecules in the TLR-4/NF-κB pathway.